'All that is behind colour': Antonioni and painting (three case studies). (1st April 2015) - Benci, Jacopo
This article explores how painting was an important visual source in the films of Michelangelo Antonioni (1912–2007), through case studies dealing with three painters whose work he was interested in and whom he was personally acquainted with: Renzo Vespignani (1924–2001), Giorgio Morandi (1890–1964) and Mark Rothko (1903–1970). The question of when and how contacts occurred between the director and the artists has been carefully analysed, by way of a detailed examination of published sources as well as unpublished eyewitness accounts.